2015
DOI: 10.1016/j.molcel.2015.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Skp2-Mediated RagA Ubiquitination Elicits a Negative Feedback to Prevent Amino-Acid-Dependent mTORC1 Hyperactivation by Recruiting GATOR1

Abstract: Summary The regulation of RagAGTP is important for amino acid-induced mTORC1 activation. Although GATOR1 complex has been identified as a negative regulator for mTORC1 by hydrolyzing RagAGTP, how GATOR1 is recruited to RagA to attenuate mTORC1 signaling remains unclear. Moreover, how mTORC1 signaling is terminated upon amino acid stimulation is also unknown. We show that the recruitment of GATOR1 to RagA is induced by amino acids in an mTORC1-dependent manner. Skp2 E3 ligase drives K63-linked ubiquitination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 40 publications
2
65
1
Order By: Relevance
“…This observation is inconsistent with a previous study showing that amino acid starvation increases the interaction between GATOR1 and RAGA [50]. SKP2 recruitment to RAGA upon amino acid stimulation is dependent on mTORC1 activity since rapamycin prevents SKP2 recruitment as well as interaction between RAGA and GATOR1 [63]. Jin et al proposed that SKP2-mediated RAGA ubiquitination is a negative feedback mechanism to prevent mTORC1 hyperactivation upon amino acid stimulation.…”
Section: Rnf152 and Skp2 E3 Ubiquitin Ligases For Ragacontrasting
confidence: 61%
See 3 more Smart Citations
“…This observation is inconsistent with a previous study showing that amino acid starvation increases the interaction between GATOR1 and RAGA [50]. SKP2 recruitment to RAGA upon amino acid stimulation is dependent on mTORC1 activity since rapamycin prevents SKP2 recruitment as well as interaction between RAGA and GATOR1 [63]. Jin et al proposed that SKP2-mediated RAGA ubiquitination is a negative feedback mechanism to prevent mTORC1 hyperactivation upon amino acid stimulation.…”
Section: Rnf152 and Skp2 E3 Ubiquitin Ligases For Ragacontrasting
confidence: 61%
“…However, RNF152 preferentially binds to the already inactive RAGA-GDP, suggesting that RNF152-mediated ubiquitination is not the primary mechanism of RAGA inactivation by GATOR1. Jin et al [63] surprisingly found that amino acids promote SKP2-mediated RAGA interaction with GATOR1. This observation is inconsistent with a previous study showing that amino acid starvation increases the interaction between GATOR1 and RAGA [50].…”
Section: Rnf152 and Skp2 E3 Ubiquitin Ligases For Ragamentioning
confidence: 99%
See 2 more Smart Citations
“…8b,c). Because the Rag GTPases serve as a metabolic switch that can reciprocally regulate AMPK and mTORC1 pathways 51 and the GATOR complex is one of the critical regulators of this switch 52,53 , hSesn2-mediated inhibition of GATOR2 and subsequent activation of GATOR1 (refs 27-29) may be the key signalling event that affects both the AMPK and mTORC1 signalling pathways.…”
Section: Discussionmentioning
confidence: 99%